LIPIDS AND THEIR MODES OF OCCURRENCE IN TWO SURFACE SEDIMENTS FROM THE DANUBE DELTA AND NORTHWESTERN BLACK SEA: IMPLICATIONS FOR SOURCES AND EARLY DIAGENETIC ALTERATION I. CARBOXYLIC ACIDS - Garcette-Lepecq A.; Bouloubassi I.; Saliot A.; Lorre A.; Point V.; Largeau C.; Derenne S. (My University, 2004)
Two surface sediments from the Danube delta and an adjacent area of the northwestern Black Sea were subjected to sequential treatment in order to obtain comprehensive qualitative and quantitative information on carboxylic acid moieties. Four acid fractions, corresponding to distinct pools, were thus obtained from each sample: (1) an organic solvent-extractable fraction corresponding to the “unbound” acids, (2) an “OH−-labile” fraction (released by classical alkaline hydrolysis of the solvent-extracted material) corresponding to the ester-bound acids, (3) a “H+-labile” fraction (obtained via subsequent acid hydrolysis of extracted and base-hydrolysed material) corresponding to amide- and/or ether-bound acids, (4) the “tightly-bound” acids released by TMAH thermochemolysis of the insoluble, non-hydrolysable and HF/HCl-resistant material. The existence of these four pools of acids reflects differences in the mode of linkage of the acid moieties and/or in the protection provided by the (macro)molecular structures into which they are incorporated.Considerable qualitative and quantitative differences were observed, for a given sample, depending on the particular pool, and large differences were also noted, for a given pool, between the two samples.The biogeochemical investigation of the carboxylic acids according to their modes of occurrence in these two surface sediments with contrasting locations provides information on (i) the relative importance of microalgal, bacterial and terrestrial contributions in surface sediments, as well as the types of species implicated and (ii) the extent of early diagenetic alteration.